Pengaruh Inovasi Produk, Promosi Media Sosial, Kualitas Pelayanan, dan Harga Terhadap Loyalitas Pelanggan E-Likuid Pada Ranggayo Vapor Sawojajar Malang - Mohammad Agus Solikin; Abdul Kodir Djaelani; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to determine and analyze the effect of Product Innovation, Social Media Promotion, Service Quality and Price on Customer Loyalty. By using the consumer population of Ranggoyo Vapor Sawojajar Malang, 95 respondents' answers were taken as the population. Using nonprobability sampling technique and using purposive sampling. The purposive sampling method uses a sampling technique with certain considerations by the researcher. The results in this study indicate that there is an effect of Product Innovation partially significantly influencing Customer Loyalty, Social Media Promotion partially does not significantly affect Customer Loyalty, Service Quality partially has a significant effect on Customer Loyalty, and Price partially has a significant effect on Customer loyalty. Keywords: Product Innovation, Social Media Promotion, Service Quality, Price, Customer Loyalty